PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEBERHASILAN USAHA PADA UMKM ROTI KACANG CAP RAJAWALI TEBING TINGGI - Agnes Paska Asima Hasibuan Hasibuan; Nalom Siagian; Jonson Rajagukguk (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
The purpose of this study was to analyze the influence of product quality and price on business success at the Rajawali Brand Peanut Bread MSME in Tebing Tinggi. The population in this study was consumers and business owners, with an unknown number of participants. The sample was determined using the Lemeshow formula, resulting in 96 respondents using a purposive sampling technique. The research variables consisted of product quality (X1) and price (X2) as independent variables, and business success (Y) as the dependent variable. The data analysis method used was multiple linear regression analysis with the help of SPSS. The results showed that product quality and price had a positive effect on business success, with the regression equation Y = 6.304 + 0.318X1 + 0.481X2. The partial test results indicated that product quality had a positive and significant effect on business success (t-test 3.264; sig. 0.002 <0.05), and price also had a positive and significant effect (t-test 4.331; sig. 0.000 <0.05). The results of the simultaneous test indicate that both variables together significantly influence business success (F-test 33.091; sig. 0.000 < 0.05). The coefficient of determination (R²) of 0.416 indicates that product quality and price explain 41.6% of the variation in business success, while the remaining 58.4% is influenced by other variables outside this study. Thus, product quality and price are proven to have a positive and significant influence on business success.